Improving Performance: Motivation of Public Service Officers and their Commitment - Guswandi Guswandi; Idayanti Nursyamsi; Sumardi Lasise; Hardiyono Hardiyono (Magister Management, Hasanuddin University, 2020)
This research aims to see the performance condition of employees who are influenced by the commitment and motivation of public service in the One-stop Administration Services Office called SAMSAT Mappanyukki Makassar in the event of Pandemic Covid-19 which demands a large-scale social restriction. This research uses a questionnaire whose data will be processed using the SmartPLS application using the path analysis method. The results found that the motivation of public service and commitment has an effect on employees ' performance amid large-scale social restrictions. The limitations of this study are that there is no discussion group forum that collects employees because conditions do not support.